From Halal Integrity to Halal Washing: Toward a Conceptual Framework of Ethical Deviation in the Halal Industry - Ayulita Ramadhani; Ira Apriyanti; Devana Anisha Indra Putri (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study develops a diagnostic framework to explain how halal integrity degrades into halal-washing within contemporary halal governance. While existing research addresses halal compliance and supply chain practices, it remains fragmented in explaining the transition from operational failure to representational deviation. Using a conceptual research design based on theory synthesis, this study reconstructs halal integrity as a multilayer system, models the process of cumulative degradation leading to institutional decoupling, and identifies structural mediators that condition this transition.The findings show that halal-washing is not merely a communication issue, but a systemic outcome of misalignment across operational practices, governance mechanisms, and institutional legitimacy under structural pressure. The study contributes by integrating fragmented halal literature and extending washing theory within a context shaped by institutional and theological implications. It further demonstrates that preventing halal-washing requires systemic intervention to ensure alignment between symbolic claims and operational reality.